Geographic determinants of Australian foreign direct investments - Kishor, Sharma; Yapa, Bandara (2007)
The volume of investment that has flowed from Australia into the outside world, and its implications for economic policy, has attracted substantial policy debate among Australian policy makers, particularly in the context of regionalisation of the world economy. Using hypotheses from investment demand model and new trade theory we investigate if market size, its growth rate, openness, regional economic integration, language and cultural similarity and the availability of knowledge capital have any impact in attracting Australian investments offshore. Our results suggest that countries which are open, have a large domestic market and stable macro-economic environment tend to attract most Australian FDI. Regional integration, and the similarity in language and culture do not have any effect in attracting FDI from Australia. This result has a significant policy implications not only for Australia, but also for other countries who are increasingly engaged in forming trading blocs like Australia-US free trade agreements (AUSFTA).